USING TIKTOK APPLICATION IN ENHANCING STUDENT SPEAKING SKILL AT THE SIXTH SEMESTER OF STKIP PGRI BANGKALAN - Rohman, Muhibur; Ulfa, Siti Maria (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Currently, technology has developed rapidly presenting various interesting features, one of the trending technologies is social media. To advance learning in the digital era, social media is very important in today's life, Tiktok is one of the well-known social media that can help improve students' speaking skills. This study aimed at finding out the process and perception of the students in using TikTok Application for their speaking skill. In this case, the researcher used a qualitative descriptive method. This research was conducted at STKIP PGRI Bangkalan, data collection using observation and interviews. The results of interviews with four sixth-semester English education study program students at STKIP PGRI Bangkalan are the source of data for this study. This study aims to determine students' perceptions of the use of Tiktok as a tool to improve speaking skills.  TikTok as a learning media is a very effective media because it has many benefits for students such as students easily get information related to courses, offers interesting features that encourage student enthusiasm for learning, this makes learning interactive, the duration of the video is short enough so that students are not easily bored, and TikTok provides English speaking exercises that can improve student speaking skills which can increase student confidence when speaking English. English speaking activities that can increase students' confidence and speaking ability and provide a better sense of confidence.